Effects of Transitional Measures Associated with EU Integration on Medical Care Access for Central and Eastern European Migrants in Germany - Castañeda, Heide (Anthropological Journal of European Cultures, 2011)
This article examines the unintended effects of policy on the cross-border health care experiences of persons from the new Central and Eastern European (CEE) states of the European Union (EU) during a time of major transition. While permitted to travel freely, most individuals from the new member states are not yet authorised to work in Germany. As a result, they face many everyday forms of exclusion, including lack of access to medical services. Drawing upon ethnographic fieldwork, this article examines experiences of patients from newly acceded CEE countries. Cross-border health care highlights instrumentality because implementation has consisted only of patchwork policies and is characterised by insufficient attention to marginalised populations, such as those who are driven to seek work abroad due to economic asymmetries across borders. In the current transitional period, evidence suggests a disconnect as social rights struggle to catch up to economic ones.